Preliminary Experience with Induction Chemotherapy In Head and Neck Malignancy from A Tertiary Cancer Centre - Joneetha Jones; Vinin N V; Linda Rag; Geetha M; Arun Narendran; Shoaib Nawaz; Nabeel Yahiya (International Journal of Pharma and Bio Sciences, 2020)
Induction chemotherapy is one among the treatment options in locally advanced head and neck malignancy either to make the tumour operable or as an organ preservation strategy. This study intends to find out the pattern of reference for induction chemotherapy and the clinical and radiological response to induction at a rural tertiary cancer centre in southern India. This was a retrospective analysis of patients who underwent induction chemotherapy from January 2014 to December 2018 at a tertiary cancer our centre. Case records, radiation and chemotherapy charts were reviewed and data was collected. A total of 27 patients under went induction chemotherapy during the given study period. The median age group was 53 years.23 patients were males and 4 were females. Induction chemotherapy schedules which were employed were a combination of Docetaxel/cisplatin and 5 fluorouracil (TPF) or a combination of cisplatin and 5 fluorouracil (PF).15 patients underwent chemotherapy with PF schedule and 12 underwent chemotherapy with TPF. Induction chemotherapy was employed before radical chemoradiation in 12 patients and before surgery in 15 patients. 96% of the patients completed the planned course of treatment. Partial response post chemotherapy was seen in 88% of patients. On follow up 81% of patients were in complete remission post planned treatment. 9 patients progressed on follow up either locally or distally. The disease free survival was found to be 55 months. Induction chemotherapy is a feasible treatment option for locally advanced head and neck malignancy aiming at a curative intent treatment. The use of induction chemotherapy is associated with significant morbidity and mortality and patients need to be closely monitored. Further trials are needed to answer the question regarding use of induction chemotherapy. Targeted therapies can also yield more promising results.